Corporate Governance, CSR disclosure and Firm performance -- based on listed companies in China - MA, Xiaojie (2019)
This dissertation estimates the association among corporate governance, CSR disclosure and enterprise performance. It emphasizes the role of strong governance mechanisms on CSR disclosure and these two factors’ interaction effect on firm performance. Three characteristics are chosen to represent internal governance mechanisms -- board size, board independence and CEO-chairman duality and one characteristic is chosen to represent external mechanisms -- the level of market competitiveness. The quantitative method is used in this dissertation based on the sample data of 198 listed enterprises from ten different industries during the year 2014-2016 in China. In terms of the association between CSR disclosure and corporate governance, the results show that the effect of board size and board independence on CSR disclosure is significantly positive while CEO duality shows a negative impact. Additionally, there is no significant influence of market competitiveness on CSR disclosure. In terms of the correlation among corporate governance, CSR disclosure and firm performance, the results exhibit that the moderating impact of board size on the relationship between CSR disclosure and firm performance is significantly positive while the moderating impact of market competitiveness is significantly negative. Additionally, board independence and CEO duality do not have moderating impact on the correlation between CSR disclosure and firm performance.